2012
DOI: 10.2478/v10078-012-0086-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Warm-Up Protocols on Jump Performance in College Football Players

Abstract: The purpose of this study was to identify the effects of warm-up strategies on countermovement jump performance. Twenty-nine male college football players (age: 19.4 ± 1.1 years; body height: 179.0 ± 5.1 cm; body mass: 73.1 ± 8.0 kg; % body fat: 11.1 ± 2.7) from the Tuzla University underwent a control (no warm-up) and different warm-up conditions: 1. general warm-up; 2. general warm-up with dynamic stretching; 3. general warm-up, dynamic stretching and passive stretching; 4. passive static stretching; 5. pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 25 publications
1
21
0
2
Order By: Relevance
“…Subjects were tested one by one on the test day, with height and body mass being taken first, before the placement of electromyography (EMG) pads on ten muscles of the subjects' dominant foot. Subsequently, a dynamic warm-up based on a protocol by Pagaduan; Pojskić; Užičanin; Babajić [58] was conducted, consisting of exercises such as butt kicks, carioca, high knees, reverse lunges, straight-leg march, power shuffle and jogging with squats. After the warm-up, the EMG sensors were connected to the pads, while reflecting markers were attached to different anatomical landmarks.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were tested one by one on the test day, with height and body mass being taken first, before the placement of electromyography (EMG) pads on ten muscles of the subjects' dominant foot. Subsequently, a dynamic warm-up based on a protocol by Pagaduan; Pojskić; Užičanin; Babajić [58] was conducted, consisting of exercises such as butt kicks, carioca, high knees, reverse lunges, straight-leg march, power shuffle and jogging with squats. After the warm-up, the EMG sensors were connected to the pads, while reflecting markers were attached to different anatomical landmarks.…”
Section: Methodsmentioning
confidence: 99%
“…Each stretching exercise consisted of 2 sets of 20 seconds with a rest interval of 10 seconds between sets. The rest interval between stretching exercises was 10 seconds [24]. The participants performed 3-5 repetitions respectively for SJ, CMJ and CMJarm with emphasis on form.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it has been found that exercise with low loads also can create an optimal environment for power production 11 . This improvement in neuromuscular function can occur through the increase of body temperature and the acceleration of metabolism 12 . In this way, although through different mechanisms, the bicycle warm-up at low intensity was also somewhat effective in improving VCMJ.…”
Section: Discussionmentioning
confidence: 99%